2008
DOI: 10.1088/0953-2048/21/9/095007
|View full text |Cite
|
Sign up to set email alerts
|

AC loss properties of MgB2multifilament wires

Abstract: We designed and fabricated two types of composite wires with 6 MgB2 filaments. One is a Cu-sheathed Nb-barrier wire and the other is a CuNi-sheathed Ta-barrier wire. The transverse-field losses of the trial wires were measured with a standardized pickup coil system in liquid helium. We evaluated the observed AC losses using two structural models, a multifilament conductor model and a hollow-cylindrical one. For the CuNi-sheathed Ta-barrier wire, the AC loss property can be explained by the usual model of mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…with simultaneously applied magnetic fields and transport currents at variable temperatures, are necessary. In the literature AC loss measurement results due to either AC transport currents [13], [14] or AC applied magnetic fields [14]- [16] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…with simultaneously applied magnetic fields and transport currents at variable temperatures, are necessary. In the literature AC loss measurement results due to either AC transport currents [13], [14] or AC applied magnetic fields [14]- [16] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…E XPERIMENTAL measurement of AC losses in superconducting wires can present significant challenges due to their relatively small magnitude, typically on the order of milliwatts. Despite these difficulties, several successful studies have reported the measurement of AC losses in wires and cables operating under stationary alternating field conditions [1]- [3]. These can be measured through the electromagnetic measurements [4], [5], the electric-heater-based calorimetric method [6], or the cryogen boil-off-rate based calorimetric method [7].…”
Section: Introductionmentioning
confidence: 99%
“…Also diffusion barriers between MgB 2 filaments and the copper stabilization may affect the transverse resistivity substantially. The most frequently used barrier material is Nb [4,[7][8][9]. Fe buffer layer was used in Ni sheathed filamentary MgB 2 tapes with 14 filaments [10].…”
Section: Introductionmentioning
confidence: 99%